Preferences of different target groups of consumers in case of furniture purchase : Sklonosti kupaca pri donošenju odluke o kupnji namještaja - Oblak, Leon (Array, 2020)
In a market environment where changes are constant, understanding customer buying behaviour is crucial for companies in order to operate both successfully and effectively. We analysed how different age groups and net monthly incomes per household influence consumer decisions in Slovenia, Serbia and Croatia in the case of furniture purchases, when the three main factors are material, price and service. Each factor was further divided into three levels. In the case of material, the respondents could choose between solid wood, chipboard and fibreboard or other materials. In the case of price, they could choose between a low, middle or high price range, and in the case of services, they could choose between pre-sales, sales and after-sales services. With conjoint analysis, we analysed the markets in Slovenia, Serbia and Croatia. The important differences in consumer buying behaviour in these three countries were discovered. The results of the research will serve as a useful basis for wood sector companies to design more successful marketing strategies, which will help them to achieve their goals in different target markets.